Return To Education In The Informal Sector In Indonesia - Riama Valentina Hutapea (Ridwan Institute, 2022)
As developing countries with large population, Indonesia face challenges in managing its human capital to support the development. The government has allocated significant amount of money in educational sector to improve the education in Indonesia that will lead to increase in Indonesian capability and competitiveness in the labour market. However, labour market in Indonesia is still dominated by the informal workers which characterized with low educated and low earning jobs. This paper aims to explore whether education bring private return to the informal workers by applying the Mincer human capital earning function and exploring the returns between gender and areas (rural or urban). The results show that education bring positive impact to the worker’s earning although the return is smaller in the informal sector than the informal one